Adoption of electronic payment system in Islamic microfinance institutions - Mohamad, Siti Aishah; Kassim, Salina (Institute for Strategic and Sustainable Accounting Development (ISSAD), Universiti Utara Malaysia (UUM), 2017)
Advancements in technology have affected financial services all over the world including in Malaysia. As the financial service industry is now dealing with the electronic payment (epayment) system, the paper-based retail payment system is considered costly, time-consuming and inefficient. The e-payment system fills in the gap of the traditional payment system by providing efficient and affordable services. Financial institutions, particularly Islamic micro-finance institutions (IMFIs) are prompted to implement the e-payment system due to the strengths of this system. Micro-enterprises can create huge potential by implementing the system which is able to give a big impact to the financial services industry in Malaysia. However, not many studies have highlighted the adoption of e-payment among IMFIs. This study aims to analyse the e-payment services offered by IMFIs by reviewing and identifying the issues and challenges in adopting the system. It also provides suggestions for the improvement of e-payment adoption by the IMFIs. A critical review of previous studies was conducted to achieve these aims. The result is expected to contribute to the enrichment of knowledge in digital financial services and will be useful for IMFIs to continuously improve their services.